Organization of Solving Problems in the Module "Linear Optics" of General Physics Based on Modern Pedagogical Technologies - B. K. Tuychibaev (Genius Journals, 2022)
In this article, there is proposed a method for solving the problems of the theme "Light return and fracture" in the general physics module "Linear optics" using new pedagogical technologies.
Keywords: Linear optics; module; pedagogical technology; questionnaire